2020
DOI: 10.1021/acsmaterialslett.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Solution-Processable Donor–Acceptor Dithienophosphole Oxide Derivatives for Multilevel Organic Resistive Memories

Abstract: A class of solution-processable, donor–acceptor-decorated dithienophosphole oxide derivatives has been successfully synthesized and employed to fabricate solution-processed resistive memory devices with a simple indium–tin oxide/active layer/aluminum structure. The intramolecular charge transfer (ICT) characters of the donor–acceptor dithienophosphole oxide derivatives were established from photophysical, solvatochromic, and computational studies. The number of conductance states in the organic memory devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Similar XRD patterns have been observed in the thin film of compound 6 , in which an intense peak at 1.68° corresponding to a d -spacing of 52.52 Å and two broad peaks from 17.68° to 24.23° and from 27.04° to 29.58° corresponding to d -spacings from 5.01 Å to 3.67 Å and from 3.29 Å to 3.02 Å, respectively, are observed. Such strong intermolecular alkyl–alkyl and π–π stacking interactions are believed to contribute to the facilitation of better molecular packing and film formation, leading to smoother surface of the films, which can be beneficial to the resistive memory performance (vide infra). , In-plane and out-of-plane grazing incidence X-ray diffraction (GIXRD) measurements have also been employed to investigate the orientation of the molecules in the spin-coated films of the representative compounds (Figures S23c–S23f in the Supporting Information). An intense peak at 1.47° and two broad peaks at 21.42° and 28.26°, corresponding to d -spacings of 60.02, 4.1, and 3.2 Å, respectively, for compound 3 , and an intense peak at 1.59° and two broad peaks at 21.68° and 27.33°, corresponding to d -spacings of 55.49, 4.1, and 3.3 Å for compound 6 in the out-of-plane diffraction patterns have been observed, similar to those observed in the XRD experiments for the thin films of compounds 3 and 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar XRD patterns have been observed in the thin film of compound 6 , in which an intense peak at 1.68° corresponding to a d -spacing of 52.52 Å and two broad peaks from 17.68° to 24.23° and from 27.04° to 29.58° corresponding to d -spacings from 5.01 Å to 3.67 Å and from 3.29 Å to 3.02 Å, respectively, are observed. Such strong intermolecular alkyl–alkyl and π–π stacking interactions are believed to contribute to the facilitation of better molecular packing and film formation, leading to smoother surface of the films, which can be beneficial to the resistive memory performance (vide infra). , In-plane and out-of-plane grazing incidence X-ray diffraction (GIXRD) measurements have also been employed to investigate the orientation of the molecules in the spin-coated films of the representative compounds (Figures S23c–S23f in the Supporting Information). An intense peak at 1.47° and two broad peaks at 21.42° and 28.26°, corresponding to d -spacings of 60.02, 4.1, and 3.2 Å, respectively, for compound 3 , and an intense peak at 1.59° and two broad peaks at 21.68° and 27.33°, corresponding to d -spacings of 55.49, 4.1, and 3.3 Å for compound 6 in the out-of-plane diffraction patterns have been observed, similar to those observed in the XRD experiments for the thin films of compounds 3 and 6 .…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Nevertheless, some major challenges still hamper the progress of supramolecular polymers towards application, particularly in terms of finding the right balance between aggregation and solubility, 13,20,21 which largely controls processability. 22,23 Accordingly, design strategies that can attenuate initial steric hindrance and allow for a more controllable self-assembly process while preserving solubility and desired functional properties are a central goal in supramolecular chemistry. 24,25 Recently, we have demonstrated that the coordination geometry serves to control molecular preorganization events that, in turn, regulate the packing modes, energy landscapes and luminescence of metallosupramolecular polymers (Scheme S3 †).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phosphole, being an organic molecular compound or as a ligand for coordination to various transition metal centers, has received increasing research interests in the past decade 14,44–60 . Desirable properties, such as tunable electrochemical characteristics, facile molecular functionalization and intermolecular packing have been observed in various classes of phosphole moieties, allowing the design of smart materials in the fields of organic electronics, 14,52,59,60 photochromism, 44,54 chemosensing, 50,51,56 and supramolecular chemistry 48,53,55,57 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phosphole, being an organic molecular compound or as a ligand for coordination to various transition metal centers, has received increasing research interests in the past decade 14,44–60 . Desirable properties, such as tunable electrochemical characteristics, facile molecular functionalization and intermolecular packing have been observed in various classes of phosphole moieties, allowing the design of smart materials in the fields of organic electronics, 14,52,59,60 photochromism, 44,54 chemosensing, 50,51,56 and supramolecular chemistry 48,53,55,57 . Recent examples have also shown that the incorporation of electron‐accepting phosphole oxide unit can lead to favorable effect on the resultant organic resistive memories, including the lowering of turn‐on voltage ( V th ), stabilization of the resistive states and generation of multilevel memory behavior 14,59,60 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation